Ischemic and Bleeding Outcomes According to the Academic Research Consortium High Bleeding Risk Criteria in All Comers Treated by Percutaneous Coronary Interventions - Daphné Doomun (Frontiers Media S.A., 2021)
Background: The Academic Research Consortium have identified a set of major and minor risk factors in order to standardize the definition of a High Bleeding Risk (ACR-HBR).Aims: The aim of this study is to stratify the bleeding risk in patients included in the Cardio-Fribourg registry, according to the Academic Research Consortium for High Bleeding Risk (ACR-HBR) definition, and to report ischemic and hemorrhagic events at 2-year of clinical follow-up.Methods: Between 2015 and 2017, consecutive patients undergoing percutaneous coronary intervention were prospectively included in the Cardio-Fribourg registry. Patients were considered high (HBR) or low (LBR) bleeding risk depending on the ARC-HBR definition. Primary endpoints were hierarchical major bleeding events as defined by the Bleeding Academic Research Consortium (BARC) grade 3–5, and ARC patient-oriented major adverse cardiac events (POCE) at 2-year follow-up.Results: Follow-up was complete in 1,080 patients. There were 354 patients in the HBR group (32.7%) and 726 patients in the low-bleeding risk (LBR) group (67.2%). At 2-year follow-up, cumulative BARC 3–5 bleedings were higher in HBR (10.5%) compared to LBR patients (1.5%, p < 0.01) and the impact of HBR risk factors was incremental. At 2-year follow-up, POCE were more frequent in HBR (27.4%) compared to LBR group (18.2%, <0.01). Overall mortality was higher in HBR (14.0%) vs. LBR (2.9%, p < 0.01).Conclusions: ARC-HBR criteria appropriately identified a population at a higher risk of bleeding after percutaneous coronary intervention. An increased risk of bleeding is also associated with an increased risk of ischemic events at 2-year follow-up.